The Veglia Altar Frontal: Notes on Its Acquisition and Subsequent Conservation - Banić, Silvija (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The altar frontal made about 1330 after the design by Paolo Veneziano (active 1333-58) is by far the most monumental of all extant embroideries worked in Venetian medieval workshops. Commissioned for the Cathedral in Krk (Veglia in Italian), a town on the island of the same name in the Kvarner (Quarnero) Bay, it remained in the Cathedral's sacristy until about 1930. Around that year and under still unclear circumstances it was purchased by Otto Bernheimer (1877-1960), who was head of one of Europe's major art-dealing companies at the time. The frontal remained in Germany until July 1964 when it was sent to the Victoria and Albert Museum in London. Since nothing has been written on why the frontal became part of one of the world's most renowned textile collections, this article primarily focuses on the intriguing story of its acquisition, and it also considers its conservation, undertaken soon after it was accessioned.